Pengaruh Dana Perimbangan dan Pendapatan Asli Daerah Terhadap Belanja Daerah Kabupaten Badung - Sari, Rosy Puspita; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2014)
Badung Regency is a regency in the province of Bali which a designation as an autonomous region since 2002 related to pilot local financial independence. Hope is the area of financial management can be perceived benefit to all parties, both public and promote the interests of the government and the public, so that the public welfare can be created. This study aims to determine the effect of simultaneous and partially fund balance and revenue to the local shopping area of Badung Regency Year 2001-2012. Design analysis is used is by using multiple linear regression. The results stated fund balance and local revenues significantly influence the shopping area of Badung Regency Year 2001-2012, either simultaneously or partially.   Keywords: balance funds, local revenues, local shopping